Basin‐Wide Oceanographic Array Bridges the South Atlantic. Issue 6 (11th February 2014) - Ansorge, I. J.; Baringer, M. O.; Campos, E. J. D.; Dong, S.; Fine, R. A.; Garzoli, S. L.; Goni, G.; Meinen, C. S.; Perez, R. C.; Piola, A. R.; Roberts, M. J.; Speich, S.; et al.
<x xml:space="preserve">Abstract</x> The meridional overturning circulation (MOC) is a global system of surface, intermediate, and deep ocean currents. The MOC connects the surface layer of the ocean and the atmosphere with the huge reservoir of the deep sea and is the primary mechanism for transporting heat, freshwater, and carbon between ocean basins. Climate models show that past changes in the strength of the MOC were linked to historical climate variations. Further research suggests that the MOC will continue to modulate climate change scenarios on time scales ranging from decades to centuries [Latif et al., 2006].